PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KERJASAMA PESERTA DIDIK PADA PEMBELAJARAN SEJARAH DI KELAS X-6 SMAN 1 BRINGIN TAHUN PELAJARAN 2022/2023 - Ulfah Faizul Himayati (Historia Pedagogia, 2024)
The aim of this research is to increase student cooperation with application Project Based Learning (PjBL) learning model in History Learning in class X-6 SMAN 1 Bringin for the 2022/2023 academic yearKeywords: Learning, Model, Pre-Literacy, Results. This research is Collaborative Class Action Research (PTKK) which was carried out with a cycle technique, each cycle consists of four stages, namely planning, action, observation, and reflection. The subjects of this research were class X-6 students at SMAN 1 Bringin totaling 35 students. The data sources in this research come from teachers, students, and history learning process. Data collection techniques used include observation, interviews and questionnaires. Based on the research results, it shows that the average percentage at the pre stage Action was 63.93%, in cycle 1 there was an increase of 5.21% to 69.14%. And in cycle 2 the percentage of student cooperation increased again by 6.43% to 75.57%. The percentage of achievements in cycle 2 stage has achieved the performance target research that has been previously determined is ≥75%. Based on the results of the research and discussion, it can be concluded that learning history using the Project Based Learning (PjBL) learning mode can increase the cooperation of class X-6 students at SMAN 1 Bringin.